KELANGSUNGAN HIDUP DAN PERTUMBUHAN LARVA IKAN BETOK (Anabas testudineus) YANG DIBERI Daphnia sp. YANG DIPERKAYA DENGAN MINYAK JAGUNG - Elva Susanti; Yulisman .; Ferdinand Hukama Taqwa (Jurnal Akuakultur Rawa Indonesia, 2015)
ABSTRACT Climbing perch larvae as one of freshwater fish commodity that have survival rate is relatively very low, one the effort to improve survival rate and also growth of climbing perch larvae which give natural feed namely Daphnia sp. was enriched by corn oil. The research conducted on August until September 2014 at Laboratorium Dasar Perikanan, Aquaculture Study Program, Faculty of Agriculture, University of Sriwijaya and extract ether analysis of Daphnia sp. and climbing perch larvae at Laboratorium Nutrisi dan Makanan Ternak, Animal Husbandry Study Program, Faculty of Agriculture, University of Sriwijaya, Indralaya. The research using completely randomized design with one way classification use six treatments and three replications. Treatments arrange by control (A0), 0.0025 mL corn oil per L of water (A1), 0.005 mL corn oil per L of water (A2), 0.01 mL corn oil per L of water (A3), 0.02 mL corn oil per L of water (A4), and 0.04 mL corn oil per L of water (A5). The parameters observed include survival rate, growth of absolute weight and long, extract ether analysis of Daphnia sp. and climbing perch larvae, physic and chemical of water. The results showed that fed of Daphnia sp. was enriched use corn oil significantly gave survival rate, growth of absolute weight and long of climbing perch larvae. Daphnia sp. was enriched with concentration 0.01 mL corn oil per L of water, proven improve survival rate, growth of absolute weight and long of climbing perch larvae. Keywords : climbing perch larvae, Daphnia sp., corn oil, survival rate, growth